Depiction of Cerebral Aneurysm Wall by Computational Fluid Dynamics (CFD) and Preoperative Illustration - Tanaka, Riki; Liew, Boon Seng; Yamada, Yasuhiro; Sasaki, Kento; Miyatani, Kyosuke; Komatsu, Fuminari; Kawase, Tsukasa; Kato, Yoko; Hirose, Yuichi (Asian Journal of Neurosurgery, 2022)
Introduction Preoperative illustration is a part of an important exercise to study the configuration, direction, and presence of any perforations, and is the weakest point in the wall of the cerebral aneurysm. The same illustration is used to study the surrounding brain structures to decide the best and safe surgical approach prior to any surgical procedure. With the evolution of the aneurysm wall study and study of flow dynamic within the involved artery and its aneurysm wall using computational fluid dynamics (CFD), a better surgical plan can be formulated to improve the flow dynamics. As one of the clinical applications of CFD, we propose a study using a composite image that combines preoperative illustration and CFD, which is traditionally widely used in neurosurgery.Methods and Materials We study the use of illustrations of the unruptured cerebral aneurysm of internal carotid-posterior communicating (ICPC) artery and anterior communicating artery (AcomA) treated at our hospital. The combinations of both preoperative illustrations and CFD images by using “ipad Pro” were used.Result and Conclusion Medical illustration in the preoperative study of unruptured cerebral aneurysm with combinations of CFD and surrounding brain structures is helpful to decide the surgical approaches and successful surgical treatments.
Keywords: cerebral aneurysm; computational fluid dynamics; preoperative illustration; preoperative planning